2020
DOI: 10.1212/wnl.0000000000010414
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Multiple Sclerosis Severity Score in a large US cohort

Abstract: Objective:To characterize disease severity and distribution of disability in pediatric-onset multiple sclerosis (POMS) and to develop an optimized modeling scale for measuring disability we performed a multi-center retrospective analysis of disability scores in 873 persons with POMS over time and compared this to previously published data in adults with multiple sclerosis (MS).Methods:Retrospective analysis of prospectively collected data collected from twelve centers of the U.S. Network of Pediatric MS Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Approximately 50% of these POMS patients were at some point treated with disease-modifying therapy (DMT), but most data stemmed from early 1976 to 2001 when none of the patients received treatment early in their disease course. To better account for the disease duration as part of the disease severity, a recent adaptation of the Multiple Sclerosis Severity Scale (MSSS) for POMS patients has been proposed (Ped-MSSS) [ 24 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
“…Approximately 50% of these POMS patients were at some point treated with disease-modifying therapy (DMT), but most data stemmed from early 1976 to 2001 when none of the patients received treatment early in their disease course. To better account for the disease duration as part of the disease severity, a recent adaptation of the Multiple Sclerosis Severity Scale (MSSS) for POMS patients has been proposed (Ped-MSSS) [ 24 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
“…In general, POMS score lower on EDSS compared to AOMS and the use of a Paediatric Multiple Sclerosis Severity Score (Ped-MSSS) has been proposed as an alternative. ( Santoro et al, 2020 ) Cognitive function was used as an outcome measure by almost two thirds of the respondents. A majority considered neuropsychological evaluation and monitoring part of routine care and, as children with MS can have significant cognitive dysfunction early in the disease course, this seems important to monitor although studies that suggest that specific therapies actually preserve cognitive function are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of children at risk of faster disability worsening is a requisite of targeted early use of these therapies, with the aim of optimising long-term outcomes in paediatric-onset MS. Prior studies have identified several potential imaging and clinical prognostic markers available in paediatric-onset MS 5 8 11–13. In this study, we used a large multi-national cohort to identify predictors of disability as early as first year after the clinical onset of paediatric MS, considering their potential for guiding the use of higher-efficacy DMTs.…”
Section: Introductionmentioning
confidence: 99%